Show and Tell Technique in Teaching Speaking Skills at SMAN 2 Palopo - Anisah Fitriani (Faculty of Education and Teacher Training of IAIN Palopo, 2020)
This research focused on using Show and Tell techniques to develop students’ speaking skills at Eleventh class of SMA Negeri 2 Palopo. The researcher used pre-experimental method. The population of this research is 157 students of XI class. The research sample is chosen purposively and got the XI IPA1 consisting of 35 students. In collecting the data, the researcher used speaking observations, divided into pre-survey and post-survey. After giving pre-survey and post-survey, this research provides pre-survey and post-survey to students. Data were analyzed using SPSS program version 20. The results of the study indicated that the use of Show and Tell Technique is effective for improving students’ speaking skills. It can be seen calculation results that the scores of students in the control class. Based on the analysis of the data it can be concluded that the teaching skills of speaking using Show and Tell Techniques at Eleventh class of SMA Negeri 2 Palopo. The implementation of this research for those who are interested in conducting research on problem statements, it is recommended to apply it to students who have basic speaking language skills and researchers hope that the results of this study can be beneficial to readers.